PENGARUH TINGKAT LITERASI KEUANGAN TERHADAP PERILAKU HIDUP HEMAT SISWA KELAS 5 SD NEGERI 4 MADE LAMONGAN - Syaifuddin, Achmad; Nurdiana, Ratna; Eryadini, Ninies (Riset Manajemen dan Akuntansi, 2025)
Financial literacy is the ability or level of understanding/knowledge a person or society has about how money works. A lack of financial literacy can significantly impact an individual's ability to manage personal finances. As a result, individuals become vulnerable to consumer behavior, unwise financial decision-making, and difficulties in achieving financial stability and security. The goal of this research is to determine the influence of the level of financial literacy on the frugal living behavior of fifth-grade students at SD Negeri 4 Made Lamongan. This study employs a quantitative research approach with a descriptive quantitative research method aimed at determining the influence of financial literacy levels on frugal living behavior among fifth-grade students at SD Negeri 4 Made Lamongan. The sample taken in this study consists of all students from class 5C at SD Negeri 4 Made Lamongan, totaling 33 students. The research instrument uses a Likert scale. In this study, the data analysis method used is simple linear regression analysis. The results of the study show that there is an influence of financial literacy levels on the frugal living behavior of fifth-grade students at SD Negeri 4 Made Lamongan.